Inflammatory Role of Toll-Like Receptors in Human and Murine Adipose Tissue - Odile Poulain-Godefroy; Olivier Le Bacquer; Pauline Plancq; Cécile Lecœur; François Pattou; Gema Frühbeck; Philippe Froguel (Mediators of Inflammation)
It was recently demonstrated that TLR4 activation via dietary lipids triggers inflammatory pathway and alters insulin responsiveness in the fat tissue during obesity. Here, we question whether other TLR family members could participate in the TLR-mediated inflammatory processes occurring in the obese adipose tissue. We thus studied the expression of TLR1, TLR2, TLR4, and TLR6 in adipose tissue. These receptors are expressed in omental and subcutaneous human fat tissue, the expression being higher in the omental tissue, independently of the metabolic status of the subject. We demonstrated a correlation of TLRs expression within and between each depot suggesting a coregulation. Murine 3T3-L1 preadipocyte cells stimulated with Pam3CSK4 induced the expression of some proinflammatory markers. Therefore, beside TLR4, other toll-like receptors are differentially expressed in human fat tissue, and functional in an adipocyte cell line, suggesting that they might participate omental adipose tissue-related inflammation that occurs in obesity.